Contradictions and realisations – a critical friendship in the pursuit of transformative PETE. Issue 3 (2nd September 2022) - Stevens, S.; Thompson, K.
ABSTRACT: The possibility for enacting transformative practices in Physical Education Teacher Education (PETE) is shaped by the social, political, and material landscape. However, it is vital we acknowledge our contributing role as PETE lecturers in this shaping process. This paper presents the authors study of their critical friendship aimed at making sense of transformative practices in PETE. The voices of recently graduated teachers telling us how they interpret and enact transformative practice are examined using a hermeneutic lens, to demonstrate our shared response and subsequent attempts to make sense of our own teaching practice. This work highlights the liminality and contradictions that both students and lecturers experience in PETE, and we are reminded that continual interrogation and exploration of the lecturer's role is essential; especially when the work of being transformative in PETE actively encourages students to do the same. We suggest this requires not only the time and space needed for introspection; but moreover, the requisite willingness and vulnerability required to consider the teacher educator's role in how students come to construct knowledge. Those within PETE should consider the use of dialogic conversations in transformative practice, not only for support, but for critically evolving practice and understanding of the profession.